Prevalence of Lower Urinary Tract Symptoms in Women Based on Bahasa Indonesia Validated ICIQ-FLUTS Long Form - Moegni, Fernandi; Retnoningrum, Endah (Indonesian Journal of Obstetrics and Gynecology, 2015)
Objective: To obtain the prevalence of women with lower urinary tract symptoms (LUTS) in Dr. Cipto Mangunkusumo National Hospital, Indonesia. Method: We conducted a descriptive and analytic study with questionnaire- based data collection. All subjects were interviewed using the conventional method and International Consultation on Incontinence Questionnaire (ICIQ) Female LUTS long form validated in Indonesian language in the gynecology outpatient clinic in Dr. Cipto Mangunkusumo Hospital. Result: Using the conventional method, proposing only one question of urinary disturbance without asking the detailed symptoms, a low prevalence of LUTS was obtained (17.3%). On the other hand, with a well-structured questionnaire using ICIQ-FLUTS long form, the prevalence of LUTS was 95.3%. This result revealed that LUTS was a common condition among Indonesian women in the study population with vaginal delivery as the common risk factor. Conclusion: Screening for LUTS using a structured questionnaire identified a significantly higher prevalence of LUTS than the conventional method. The ICIQ-FLUTS long form validated in Indonesian language is a robust questionnaire that can be recommended for use in epidemiological research as well as routine clinical practice. Keywords: ICIQ FLUTS long form, Indonesia, LUTS, prevalence, women